Early diversion and empowerment policing: evaluating an adult female offender triage project - Brennan, Iain (Policing and society, 2018)
This paper provides an evaluation of a police pilot early-diversion scheme for adult females who were arrested for low-severity offences using a natural experiment design. The intervention is novel in that it diverts arrestees to a women’s centre for assistance to address their criminogenic needs rather than process them through the criminal justice system. The intervention is timely and attractive given its rehabilitative features and its potential for reducing demand on the criminal justice system through community resolution. The study found a promising effect of the intervention on rates of rearrest and daily risk of rearrest over a 12-month follow-up period, but a higher frequency of rearrest among those of the intervention group who were rearrested. The findings are discussed in relation to the political context, theoretical background and police performance and the gendered dynamics of offending.